EFFICIENCY OF UTERINE BALLOON TAMPONADING IN THE PREVENTION AND TREATMENT OF MASSIVE POSTPARTUM HYPOTONIC BLEEDINGS - N.A. Urinbayeva; G.S. Babadjanova; Sh.Kh. Mahkamova (Scholar Express Journals, 2022)
The purpose of the study was to evaluate the effectiveness of the balloon tamponade method to improve the results of treatment of women with hypotonic postpartum hemorrhage after spontaneous vaginal delivery. For the study, we selected the birth histories of 60 patients with postpartum hemorrhage after vaginal delivery. The study assessed primary outcomes, i.e. the volume of blood loss in the III and early postpartum period of labor, as well as secondary outcomes - the frequency of blood transfusion, the use of additional uterotonics, the use of additional surgical procedures (vessel ligation, hysterectomy, etc.). studies have shown that the use of balloon tamponade for postpartum hemorrhage of more than 500 ml and up to 1000 ml has a faster uterotonic effect than the traditional method. It helps to reduce primary and secondary complications arising from postpartum hemorrhage and helps to reduce the frequency of hysterectomy due to hypotonic bleeding
Keywords: Uterotonic effect; balloon tamponading; permissible values; hemostasis system